DUCT reveals architectural mechanisms contributing to bile duct recovery in a mouse model for Alagille syndrome - Hankeova, Simona; Salplachta, Jakub; Zikmund, Tomas; Kavkova, Michaela; Van Hul, Noémi; Brinek, Adam; Smekalova, Veronika; Lázňovský, Jakub; Dawit, Feven; Jaros, Josef; Bryja, Vítězslav; Lendahl, Urban; et al. (eLife, 2021)
Organ function depends on tissues adopting the correct architecture. However, insights into organ architecture are currently hampered by an absence of standardized quantitative 3D analysis. We aimed to develop a robust technology to visualize, digitalize, and segment the architecture of two tubular systems in 3D: double resin casting micro computed tomography (DUCT). As proof of principle, we applied DUCT to a mouse model for Alagille syndrome (Jag1Ndr/Ndr mice), characterized by intrahepatic bile duct paucity, that can spontaneously generate a biliary system in adulthood. DUCT identified increased central biliary branching and peripheral bile duct tortuosity as two compensatory processes occurring in distinct regions of Jag1Ndr/Ndr liver, leading to full reconstitution of wild-type biliary volume and phenotypic recovery. DUCT is thus a powerful new technology for 3D analysis, which can reveal novel phenotypes and provide a standardized method of defining liver architecture in mouse models.
Keywords: Alagillův syndrom; Alagille Syndrome; Animals; myši transgenní; Bile Ducts; zvířata; X-Ray Microtomography; rentgenová mikrotomografie; Mice; Disease Models, Animal; modely nemocí na zvířatech; žlučové cesty; Mice, Transgenic; myši